Negotiations at Work Field Practice of Shariah Banking Students in Conventional Banking - Hendrianto, Hendrianto; Umam, Khairul; Ulmawandri, Juniko; Nurcahyati, Dwi (Jurnal Ekonomi dan Perbankan Syariah, 2024)
This research aims to analyze the implementation of negotiations in these negotiations, analyze the implementation of student internship activities, and determine the satisfaction of Conventional Financial Institutions with the Performance of Student Interns. This research is a Mix Method. The data collection techniques used were observation, interviews, documentation and questionnaires. The research results show that the negotiation strategy and planning carried out by the IAIN Curup Sharia Banking Study Program was carried out with a win-win strategy with planning carried out through discussions among Sharia Banking lecturers and the formation of an internship committee. The implementation of negotiations in negotiations takes place through the stages of exchanging information, bargaining and commitment. The implementation of internship activities is carried out in three parts, namely the opening in the form of a briefing preparing intern students for work. Carrying out internship activities helps serve customers and assists the work of other employees. Meanwhile, closing is to evaluate the service activities provided on that day. The satisfaction of conventional financial institutions with the performance of Islamic Banking Study Program intern students at IAIN Curup is in the range of 80-100% with statements of very satisfaction.